2015
DOI: 10.1002/cmdc.201500241
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Transfer from Ligands Hyperpolarized by Dissolution Dynamic Nuclear Polarization for Screening in Drug Discovery

Abstract: Nuclear magnetic resonance (NMR) spectroscopy is a valuable technique for ligand screening, because it exhibits high specificity toward chemical structure and interactions. Dissolution dynamic nuclear polarization (DNP) is a recent advance in NMR methodology that enables the creation of non-equilibrium spin states, which can dramatically increase NMR sensitivity. Here, the transfer of such spin polarization from hyperpolarized ligand to protein is observed. Mixing hyperpolarized benzamidine with the serine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 34 publications
0
51
1
Order By: Relevance
“…Due to the hyperpolarization of the ligand, polarization transfer to the protein leading to visible signals even in a single scan can be expected (Min et al 2015). Enhanced signals in spectral regions characteristic of the protein, in particular side-chain protons, are indeed readily seen upon admixing of DHFR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the hyperpolarization of the ligand, polarization transfer to the protein leading to visible signals even in a single scan can be expected (Min et al 2015). Enhanced signals in spectral regions characteristic of the protein, in particular side-chain protons, are indeed readily seen upon admixing of DHFR.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrafast 2D NMR spectra of polarization transferred from water to exchangeable amide protons in proteins were reported (Olsen et al 2016). In our previous work, we have demonstrated that polarization transfer from a specifically binding hyperpolarized ligand shows a spectrum similar to the frequency dependence of the transfer of saturation from the protein to the ligand (Min et al 2015). Using D-DNP hyperpolarization, a two-step polarization transfer between competitively binding ligands, mediated by the protein, can be observed similar to the Interligand NOE for Pharmacophore Mapping (INPHARMA) experiment (Orts et al 2009; Lee et al 2012).…”
Section: Introductionmentioning
confidence: 92%
“…8 Transfer of ligand hyperpolarization via nuclear Overhauser effect to the protein or to a competing ligand can further provide a means to prove binding and potentially characterize the binding site. 9,10 While the latter may already extend beyond the most basic screening application, a parameter that is often of interest in drug discovery is the dissociation constant of the ligand for the protein. Typically, the determination of binding affinities using NMR spectroscopy is achieved by a titration of protein or ligand concentration.…”
Section: Introductionmentioning
confidence: 99%
“…F spectra of TFA after mixing with hyperpolarized water using the pulse sequence in Figure 1a. b) Stacked plots of the successively acquired 19 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 11 parameter is σ = 2.6110 -4 s -1 M -1 for the data set shown here.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the cross-relaxation parameter (3) can be defined, which takes on the same value irrespective of the concentrations in the sample. The 19 F signal intensities were modeled during each time period free of rf pulses with analytical solutions of these equations with arbitrarily selectable initial signal intensities for both spins:…”
Section: Methodsmentioning
confidence: 99%